Serbian translation of the Three Domains of Disgust Scale (TDDS): a pilot study - Rokvic, Nikola; Jovović, Radivoje (Engrami, 2022)
Disgust is a universal emotion representing a need to withdraw from revolting stimuli. The adaptationist paradigm dictates that there are three domains of disgust, the moral, sexual and traditional pathogen disgust. This has been operationalized as the Three Domains of Disgust Scale (TDDS). In two studies we have tested the student population in order to first examine the structure of the questionnaire with exploratory and then confirmatory factor analysis. We have achieved appropriate model fit but with eliminating five items in order to preserve the original three factor structure. We have also detected the expected relationship with other measure of disgust already adapted to the Serbian language. In conclusion the TDDS is viable for use in the Serbian language albeit in a shortened version.
Keywords: disgust; sexual disgust; moral disgust; pathogen disgust; TDDS